Managing participation in the adult ESL classroom: engagement and exit practices. Issue 2 (4th May 2018) - Reddington, Elizabeth
Abstract: While there has been long-standing interest in identifying teacher practices for facilitating participation, less attention has been paid to what might be termed the 'participation paradox', or the necessity of engaging in and disengaging from interactions with individual students to create opportunities for both extended and even participation. In this study, I describe the interactional work undertaken by one teacher to navigate the paradox during a whole-class communicative activity in an adult English as a Second Language class. Highlighting the coordinated use of verbal and non-verbal resources, I demonstrate how the teacher uses two sets of practices to engage in and carefully exit from dyadic exchanges. I argue that both sets of practices reflect the teacher's orientation to involving not only the currently addressed student but also the unaddressed others. Findings contribute to a growing body of work that seeks to explicate the 'how' of (second language) teaching.